2017
DOI: 10.3390/antiox6040079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Taurine on the Recovery from Eccentric Exercise-Induced Muscle Damage in Males

Abstract: Eccentric exercise is known to bring about microstructural damage to muscle, initiating an inflammatory cascade involving various reactive oxygen species. This, in turn, can significantly impair physical performance over subsequent days. Taurine, a powerful endogenous antioxidant, has previously been shown to have a beneficial effect on muscle damage markers and recovery when taken for a few days to several weeks prior to eccentric exercise. However, to date no studies have looked at the effects of supplementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
4
21
0
2
Order By: Relevance
“…However, a later study by the same group [115] using an identical taurine supplementation protocol found that soreness during a 4-day recovery period after eccentric elbow flexion (2 × 20, MVC) was attenuated in the recreationally active male participants who consumed taurine. These results were supported by McLeay and colleagues [116], who reported that recreationally active males who consumed taurine (0.1 g/kg/day) for 3 days after a bout of eccentric elbow flexion exercise (6 × 10, MVC) experienced faster recovery of eccentric torque production relative to those who consumed placebo. Thus, taurine supplementation shows promise as a nutritional adjunct to reduce symptoms of EIMD, though more information is needed to determine optimal dosing patterns (Table 4).…”
Section: Main Textsupporting
confidence: 67%
“…However, a later study by the same group [115] using an identical taurine supplementation protocol found that soreness during a 4-day recovery period after eccentric elbow flexion (2 × 20, MVC) was attenuated in the recreationally active male participants who consumed taurine. These results were supported by McLeay and colleagues [116], who reported that recreationally active males who consumed taurine (0.1 g/kg/day) for 3 days after a bout of eccentric elbow flexion exercise (6 × 10, MVC) experienced faster recovery of eccentric torque production relative to those who consumed placebo. Thus, taurine supplementation shows promise as a nutritional adjunct to reduce symptoms of EIMD, though more information is needed to determine optimal dosing patterns (Table 4).…”
Section: Main Textsupporting
confidence: 67%
“…Compounds such as GSH and coenzyme A may reduce the benefits of taurine, as they are utilized to synthesis other compounds. Keeping optimal taurine levels in the muscle cell is difficult, and facilitating taurine synthesis in the cells may advance the role of ROS-induced benefits through taurine synthesis instead of ROS-induced muscle damage (De Luca et al, 2003;Ito et al, 2010;McLeay et al, 2017).…”
Section: Taurine's Role In Exercise Performancementioning
confidence: 99%
“…Tauryna jest także suplementem szeroko wykorzystywanym w sporcie. Chroni bowiem mięśnie przed urazami w trakcie wysiłku fizycznego, jak również przyspiesza ich regenerację po wysiłku ekscentrycznym [69]. Zhang i in.…”
Section: Taurynaunclassified